"Evaluación de las características fisico-químicas y sensoriales de la jalea de piña (Ananas comosus), zumo de maracuyá (Passiflora edulis) y pulpa ersidual del concentrado de maracuyá - Zamora Párraga, Ariana Yomira (2019)
The objective of this research was to evaluate the physical-chemical and sensory characteristics of pineapple jelly (Ananas comosus), passion fruit (Passiflora edulis) and pulp residues of passion fruit concentrate added in different proportions. Physical analysis, sensory profile and fungi and yeast analysis were applied to the best treatment. A completely randomized experimental design (DCA) was applied, with 4 treatments and 4 repetitions. The data obtained were analyzed in the statistical software SPSS, determining in the first instance the normal distribution or not of the reported values, using the Kolmogorov-Smirnov test with a 5% probability. Checking that the experimental data are not distributed in a normal way, Friedman's nonparametric test was used, which showed that: the null hypothesis was accepted: When using different treatments and concentrations of pineapple (Ananas comosus), juice of passion fruit (Passiflora edulis) and residual pulp of the passion fruit concentrate to obtain jelly, there is no difference between the characteristics of the treatment groups. The sensory profile of T2 (70/20/10), of pineapple jelly, passion fruit juice and residual pulp of the passion fruit concentrate, obtained the highest preference index of 29%. Where, it presented a lot of pineapple and passion fruit smell, a lot of pineapple and passion fruit flavor, while acid and orange color was quite, in addition, a lot of yellow and moderate caramel color. In the analysis of fungi and yeast presented less than> 10 mold propagating units, therefore, according to NTE INEN 1529-10: 2013 is within the permitted limits being suitable for human consumption